Keeping financial records - Kaliski, Burton S. (South-Western Educational Pub, 2006)
Master financial record keeping with KEEPING FINANCIAL RECORDS FOR BUSINESS! This up-to-date textbook equips you with a broad knowledge of business operations and the basic skills you need to keep better financial records. And developing record-keeping skills is far easier using he authors' step-by-step approach.